Disease-specific survival for patients with multiple myeloma: significant improvements over time in all age groups. Issue 12 (December 2014) - Libby, Edward; Garcia, David; Quintana, Dulcinea; Fekrazad, M. Houman; Bauman, Julie; Ebaid, Ala; Hromas, Robert; Rabinowitz, Ian; Wiggins, Charles
Abstract This study analyzed the survival of patients with multiple myeloma. Surveillance, Epidemiology, and End Results (SEER) and Centers for Disease Control and Prevention (CDC) databases were queried to calculate myeloma cause-specific survival curves by the Kaplan and Meier product-limit method. The Cox proportional hazards model was used to assess univariate and multivariate predictors of myeloma cause-specific survival. The outcome of interest was death due to myeloma. Results from a Cox proportional hazards model restricted to age and time period at diagnosis demonstrated that the magnitude of improvement in survival by time period varied by age at diagnosis. Among patients under 60 years at diagnosis, hazard ratios for myeloma cause-specific death decreased by more 50% from the first interval of observation to the last. Hazard ratios decreased during the study period by 39% among patients 60–69 years of age and by 27% among patients who were 70 years of age and older. Survival is improving in patients with myeloma of all ages.